2017
DOI: 10.17507/tpls.0710.02
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of Reader Response Journals on the Quality of Teacher Trainees’ Responses to Literary Works

Abstract: Abstract-The present study investigated the effects of writing reader response journals (RRJ) on the quality of responses to literary works assigned. The study is underpinned by Rosenblatt's Reader Response Theory, literacy principles, and sociocultural views. The study assumes that readers' responses to literature involve critical and aesthetic reading-writing (literacy) events that are collaboratively constructed. The study involved an intact group (N=22) comprising EFL teacher trainees of a private educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In line with the study above, Iskhak, Saleh, Sofwan, Hartono (2017) also investigated the effects of reader-response journals on the quality of teacher trainees' responses to literary works. The study followed Rosenblatt's reader response theory, literacy principles, and sociocultural views, which resulted in three findings.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In line with the study above, Iskhak, Saleh, Sofwan, Hartono (2017) also investigated the effects of reader-response journals on the quality of teacher trainees' responses to literary works. The study followed Rosenblatt's reader response theory, literacy principles, and sociocultural views, which resulted in three findings.…”
Section: Introductionmentioning
confidence: 93%
“…Scholars believed one effective approach that can be used in teaching literature is reader-response approach; hence study about reader-response and literature has been done extensively (Febriani, 2019;Iskhak, Saleh, Sofwan, Hartono, 2017;Trisnawati, 2009). Firstly, in her study, Febriani (2019) stated that by applying reader-response approach in a literature class, the students are able to express not merely their personal feelings (like, dislike, sad, unhappy feelings, and so on), but they had also showed that they had a good start to think critically upon literary works.…”
Section: Introductionmentioning
confidence: 99%
“…She added that discussion questions in the RRA gave the students the idea of how to express their ideas and thought on a piece of paper. Related to this view, Iskhak et al (2017) agreed that the Reader-Response theory offered reading-writing activities.…”
Section: Kinds Of Approaches Used To Teach Literature In the Efl Clas...mentioning
confidence: 99%
“…It shows a relationship between the text and the reader's self, which helps create meaning exploration. Exploring meaning also requires inter textualization and the association of readers with their own life experiences to interpret the text (Iskhak et al, 2017).…”
Section: N P R E S S 79mentioning
confidence: 99%